Study of micro hydromechanical deep drawing of SUS304 circular cups by an ALE model. (2017) - Luo, Liang; Wei, Dongbin; Jiang, Zhengyi; Zhou, Cunlong; Huang, Qingxue; Huang, Zhichao
Abstract: Accurate estimation of hydraulic pressure on the blank is important for micro hydromechanical deep drawing simulation. An Arbitrary Lagrange Eulerian (ALE) simulation model that considers strong fluid-solid interaction (FSI) was generated to accurately predict the hydraulic pressure on the blank. The changeable pressure significantly affects the drawn cup's quality regarding wall thickness. Both the minimum and the maximum wall thicknesses in the ALE model are significantly different from that in a conventional model with a simple pressure load. The relationship between the maximum thickness and the hydraulic pressure in the ALE model is similar to that from the experimental results while reverse to that from the conventional simulation model. The ALE model provides more precise hydraulic pressure on the blank and accurate prediction of the drawn cups' quality compared with the conventional model.